Heptoblastoma as a Rare Cause of Precocious Puberty (Ibrahim Medical College Journal, 2009)
A 15-month old boy presented with an abdominal swelling and early development of secondary sexual characteristics for the last 5 months. The mass was initially suspected to be of adrenal origin. Radiological and biochemical (hormonal) findings diagnosed the case to be a hepatoblastoma later confirmed by histopathological examination. Hepatoblastoma, an aggressive primary liver tumor, is a rare form of childhood malignancy and a rare cause of precocious puberty compared to the more common adrenal causes including congenital adrenal hyperplasia, adrenal tumors and the testicular tumors. Thus, when virilization occurs postnatally in boys, or girls presenting with ambiguous genitalia at birth, a virilizing adrenocortical tumor is usually given the first consideration (according to its frequency of incidence), followed by CNS causes. Rarely does one think of the other possibilities. This report describes the typical presentations and clinical features of hepatoblastoma highlighting its usual radiological features. Ibrahim Med. Coll. J. 2007; 1(2): 28-32 Key Words: Hepatoblastoma, precocious puberty, imaging features.   doi: 10.3329/imcj.v1i2.2907